Gender-based opportunity structure in the energy sector: a literature review on women’s networking and mentoring - Daniela Lazoroska; Jenny Palm; Anna-Riikka Kojonsaari (Energy, Sustainability and Society)
Abstract Background While the energy system is recognized as the largest contributor to climate disruption, the bulk of the sustainability-oriented interventions are made through technologies rather than employment equity and social justice issues. Emergent research points to the critical role of increasing the number of women and other minoritized groups in the energy sector, which could have a cultural, economic, and environmental impact. Nevertheless, how inclusion and diversity in the sector are to be achieved is not clear. Main text This article is a result of a structured literature review of earlier research focusing on gender in professional networks and mentoring programs within the energy sector. Professional networks and mentoring have been identified as some of the tools employed for increasing gender diversity in the sector. We seek to understand how gender has been integrated, what the main barriers and enablers for women are, and what strategies organizations have applied to achieve gender balance so that men and women face equal opportunities to partake in and influence decisions concerning the energy system. Conclusion We found that women’s exclusion is not recognized as a problem that needs to be acknowledged, monitored, or addressed by the energy sector or policymakers. Professional mentoring and networking have largely been employed to fill the career advancement and diversity gaps left untackled by the energy sector or policymakers. Opportunities for women to be meaningfully included in energy systems decision-making are still limited and fragmented. Furthermore, this lack of recognition is mirrored in energy research. We identified a concerning lack of evidence-based findings on the topic of women’s networking and mentoring in the energy sector. We thus call for in-depth, qualitative, and critical examinations of how opportunities for women and other minoritized groups are generated on both the policy and practice level.